Retention of the antibiotic teicoplanin on a hydromer-coated central venous catheter to prevent bacterial colonization in postoperative surgical patients - Bach, Alfons; Darby, David R.; Böttiger, Bernd W.; Böhrer, Hubert; Motsch, Johann; Martin, Eike (Intensive care medicine, 1996)
Antibioticcoated intravascular catheters may be an effective means of decreasing bacterial colonization and subsequent catheter-related infection. The present study was designed to investigate the retention of the antibiotic teicoplanin on a hydromer-coated intravenous catheter and the effect of this antibiotic coating on catheter bacterial colonization.